P15 Does an interferon-gamma release assay change practice in patients referred to clinic for possible latent tuberculosis infection?. (2nd December 2011) - Tiernan, J F; Gilhooley, S; Jones, M E; Chalmers, J D; McSparron, C; Laurenson, I; Stevenson, J; Hill, A T
Abstract : Introduction and Objectives: Suspected latent tuberculosis infection (LTBI) is a common reason for referral to TB specialist clinics. This is becoming increasingly frequent since the introduction of newer immunomodulatory drugs. Interferon-gamma release assays (IGRAs) are more sensitive and specific than tuberculin skin tests (TSTs) for diagnosing LTBI. NICE guidelines (2011) recommend considering IGRA testing to diagnose LTBI in those with positive TST or in whom TST may be less reliable. The aim of this study is to determine if IGRA changes practice in the management of cases referred to a TB specialist clinic for possible LTBI. Methods: A prospective study was carried out over a 29-month period. All adult patients who had three interventions [TST, chest x-ray (CXR) & QuantiFeron TB-Gold (QFT)] were included. The original decision to proceed with TB chemoprophylaxis was made by TB team consensus, based on the clinical history and TST alone. Cases were then analysed with the addition of QFT to determine if the QFT had altered management. An independent TB physician subsequently reviewed the cases. Each case was then analysed on the presumption of QFT as a "gold-standard" vs the original clinician-based approach. Results: 204 patients were included. Sixty-eight were immunocompromised. One hundred and nine were referrals from other medical specialties, with the remaining 95 from other agencies. One hundred and eighteen patients had a positive TST and 84 had a negative TST. In those with positive TST, 35 (30%) had a positive QFT and 83 (70%) had a negative QFT. Practice changed in 77 (65%) cases with positive TST, all of whom avoided TB chemoprophylaxis due to negative QFT. Of the 68 immunocompromised patients, 16 (24%) underwent change of practice (Abstract P15 figure 1 ). There were no discrepancies between the original team and the independent TB physician. "Gold-standard" analysis revealed 12 discrepant cases (6%). No cases of active TB have developed in the study population, with maximum follow-up period of 36 months. Conclusions: This study demonstrates a significant change of clinical practice in the management of possible LTBI with the recent introduction of QFT testing. Our findings support the NICE 2011 recommendations with regard to TST-positive patients and immunocompromised patients.